2018
DOI: 10.1007/s13738-018-1543-4
|View full text |Cite
|
Sign up to set email alerts
|

Fast dispersive liquid–liquid microextraction based on magnetic retrieval of in situ formed an ionic liquid for the preconcentration and determination of benzophenone-type UV filters from environmental water samples

Abstract: This work concerns the development of a novel and rapid in situ dispersive liquid-liquid microextraction method for magnetic retrieval of ionic liquid as a new approach for the separation of benzophenone type (BP-type) UV filters via quantification using UPLC with PDA detection. The analytes determined in this study were a group of three benzophenones: 2,4-dihydroxybenzophenone (BP1), 2,2′,4,4′-tetrahydroxybenzophenone (BP2) and 2-hydroxy-4-metoxybenzophenone (BP3). The hydrophilic ionic liquid found suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Another optimized DLLME method that uses an ionic liquid, in situ-formed, based on didecyldimethylammonium chloride (DDAC) was proposed by Ziemblińska-Bernart, et al They concluded that the optimal ratio of DDAC to NaClO 4 was 1:2. Samples taken from a depth of 15–30 cm from lakes and recreational beaches were free of the examined BPs [ 83 ]. The in situ formation coupled with the magnetic retrieval makes this method appealing but as mentioned above, DLLME methods using IL can be substituted for using DES.…”
Section: Sample Preparation For Benzophenone Detectionmentioning
confidence: 99%
“…Another optimized DLLME method that uses an ionic liquid, in situ-formed, based on didecyldimethylammonium chloride (DDAC) was proposed by Ziemblińska-Bernart, et al They concluded that the optimal ratio of DDAC to NaClO 4 was 1:2. Samples taken from a depth of 15–30 cm from lakes and recreational beaches were free of the examined BPs [ 83 ]. The in situ formation coupled with the magnetic retrieval makes this method appealing but as mentioned above, DLLME methods using IL can be substituted for using DES.…”
Section: Sample Preparation For Benzophenone Detectionmentioning
confidence: 99%
“…Nowadays, sample preparation technology has been developing towards high efficiency, rapidity, environmental sustainability, economy, and miniaturization [1,2]. Microextraction technologies, including solid phase microextraction (SPME) [3,4] and liquid phase microextraction (LPME) [5][6][7][8], have obtained great attention and overcome some intrinsic disadvantages such as consumption of many organic solvents, cumbersome steps, and time-consuming and laborious processes in traditional sample preparation techniques. Accordingly, microextraction technology, with its advantages of simplicity and rapid extraction equilibrium, plays a more and more important role in environmental, biological, and medical analysis [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the recovery process is relatively difficult for lighter-density extractants than water. Accordingly, solidification of the floating organic droplet (SFO) [12][13][14][15][16][17][18], collection by nanoparticles [5,19], and the upper narrow neck of the vessel [20,21] are usually employed for the recovery of those light extractants. In the SFO procedure, the extractant droplet with a high solidification point can be collected and transferred easily after extraction by solidification at a lower temperature [13].…”
Section: Introductionmentioning
confidence: 99%
“…While many toxic organic solvents, such as dichloromethane, carbon tetrachloride, chlorobenzene, were used in traditional DLLME, development of effective, cheap, and ecofriendly extractant is of significance to meet the requirements of green analytical chemistry. Ionic liquids have unique physical and chemical properties, such as wide liquid range, low vapor pressure at room temperature, high solvation capabilities, structure controllability, which have great application potential in sample preparation [11–13]. However, the synthesis and purification of ionic liquids are difficult, resulting in their high costs that limit their wide applications [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids have unique physical and chemical properties, such as wide liquid range, low vapor pressure at room temperature, high solvation capabilities, structure controllability, which have great application potential in sample preparation [11–13]. However, the synthesis and purification of ionic liquids are difficult, resulting in their high costs that limit their wide applications [11,12]. Deep eutectic solvents (DESs) are a kind of novel green solvent that are prepared by some hydrogen bond acceptors (HBAs, such as quaternary ammonium salts, choline chloride) and hydrogen bond donors (HBDs, such as amides, carboxylic acids, and polyols) with a certain stoichiometric ratio.…”
Section: Introductionmentioning
confidence: 99%